Dissemination mechanisms of NDM genes in hospitalized patients. Issue 1 (30th March 2021) - Zhai, Yuting; Lee, Shinyoung; Teng, Lin; Ma, Zhengxin; Hilliard, Nicole B; May, Robert J; Brown, Scott A; Yu, Fahong; Desear, Kathryn E; Cherabuddi, Kartik; Rand, Kenneth H; Morris, J Glenn; et al.
Abstract: Background: NDM-producing Enterobacteriaceae are a major clinical concern worldwide. We characterized NDM-positive pathogens isolated from patients and assessed the dissemination patterns of the bla NDM genes in a hospital setting. Methods: Eleven NDM-positive Enterobacteriaceae (three Enterobacter hormaechei, six Klebsiella pneumoniae and two Escherichia coli ) were isolated from nine patients over a 1 year period. Antimicrobial susceptibility was assessed by MICs. A combination of short- and long-read WGS was used for genome analysis. Clinical treatment history of patients was linked with genetic features of individual isolates to investigate the dissemination patterns of the bla NDM genes and NDM-positive strains. Results: bla NDM in clonal K. pneumoniae were transmitted between two patients. In other instances, an identical IncC plasmid encoding NDM-1 was transmitted between E. coli and K. pneumoniae isolated from the same patient, and an IncX3 plasmid, carrying bla NDM-1 or bla NDM-5, was harboured in non-clonal E. hormaechei . Varying patterns of IS elements were identified as a critical transmission mechanism in association with bla NDM genes. Conclusions: Multiple transmission patterns were identified in hospitalized patients, including dissemination of clonal bacterial strains carrying resistance genes and horizontal transfer of resistance genes among divergent bacterial strains. Controlling spread of NDM is complex: while attention to standard infection control practices is critically important, this needs to be matched by aggressive efforts to limit unnecessary antimicrobial use, to minimize the selection for and risk of transfer of 'high mobility' resistance genes among Enterobacteriaceae.